2022
DOI: 10.1186/s13054-022-04077-y
|View full text |Cite|
|
Sign up to set email alerts
|

The future of intensive care: delirium should no longer be an issue

Abstract: In the ideal intensive care unit (ICU) of the future, all patients are free from delirium, a syndrome of brain dysfunction frequently observed in critical illness and associated with worse ICU-related outcomes and long-term cognitive impairment. Although screening for delirium requires limited time and effort, this devastating disorder remains underestimated during routine ICU care. The COVID-19 pandemic brought a catastrophic reduction in delirium monitoring, prevention, and patient care due to organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 93 publications
(100 reference statements)
1
42
0
7
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified a citation error in the Future Delirium Monitoring section and the author name Shawniqua Williams Roberson. The family name contained an error.…”
Section: Correction To: Crit Care (2022) 26:200 Https://doi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified a citation error in the Future Delirium Monitoring section and the author name Shawniqua Williams Roberson. The family name contained an error.…”
Section: Correction To: Crit Care (2022) 26:200 Https://doi...mentioning
confidence: 99%
“…The citation and reference and author group has been updated in this correction article and the original article [ 1 ] has been corrected.…”
Section: Correction To: Crit Care (2022) 26:200 Https://doi...mentioning
confidence: 99%
“… 12 13 More delirium occurs when delirium monitoring is reduced. 13 Therefore, as a precursor state of delirium, timely prevention and detection of SSD are of great significance to patients. 12 14 …”
Section: Introductionmentioning
confidence: 99%
“…12 13 More delirium occurs when delirium monitoring is reduced. 13 Therefore, as a precursor state of delirium, timely…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, advances in organizational safety should contribute to reducing the administrative burden of clinicians, incorporate evidence-based strategies, and leverage the development of an “intelligent clinical environment” (3, 4). This environment would promote a high-level of organizational safety in the ICU, intended to reduce clinicians’ cognitive load, minimize diagnostic and treatment errors in the ICU, and facilitate active participation and inclusion of patients and families within care teams at the bedside (3, 5). The paradigm is shifting in the critical care environment.…”
mentioning
confidence: 99%